Exploring the Clinical and Genetic Spectrum of Steroid Resistant Nephrotic Syndrome: The PodoNet Registry - Agnes Trautmann; Beata S. Lipska-Ziętkiewicz; Franz Schaefer (Frontiers Media S.A., 2018)
Background: Steroid resistant nephrotic syndrome (SRNS) is a rare condition, accounting for 10-15% of all children with idiopathic nephrotic syndrome. SRNS can be caused by genetic abnormalities or immune system dysfunction. The prognosis of SRNS varies from permanent remission to progression to end-stage kidney disease, and post-transplant recurrence is common.Objectives: The PodoNet registry project aims to explore the demographics and phenotypes of immune-mediated and genetic forms of childhood SRNS, to assess genotype-phenotype correlations, to evaluate clinical management and long-term outcomes, and to search for novel genetic entities and diagnostic and prognostic biomarkers in SRNS.Methods: In 2009, an international registry for SRNS was established to collect retro- and prospective information on renal and extrarenal disease manifestations, histopathological and genetic findings and information on family history, pharmacotherapy responsiveness and long-term outcomes. To date, more than 2,000 patients have been enrolled at 72 pediatric nephrology centers, constituting the largest pediatric SRNS cohort assembled to date.Results: In the course of the project, traditional Sanger sequencing was replaced by NGS-based gene panel screening covering over 30 podocyte-related genes complemented by whole exome sequencing. These approaches allowed to establish genetic diagnoses in 24% of the patients screened, widened the spectrum of genetic disease entities presenting with SRNS phenotype (COL4A3-5, CLCN5), and contributed to the discovery of new disease causing genes (MYOE1, PTPRO). Forty two percent of patients responded to intensified immunosuppression with complete or partial remission of proteinuria, whereas 58% turned out multi-drug resistant. Medication responsiveness was highly predictive of a favorable long-term outcome, whereas the diagnosis of genetic disease was associated with a high risk to develop end-stage renal disease during childhood. Genetic SRNS forms were generally resistant to immunosuppressive treatment, justifying to avoid such pharmacotherapies altogether once a genetic diagnosis is established. Even symptomatic anti-proteinuric treatment with RAS antagonists seems to be challenging and of limited efficacy in genetic forms of SRNS. The risk of post-transplant disease recurrence was around 30% in non-genetic SRNS whereas it is negligible in genetic cases.Conclusion: In summary, the PodoNet Registry has collected detailed clinical and genetic information in a large SRNS cohort and continues to generate fundamental insights regarding demographic and etiological disease aspects, genotype-phenotype associations, the efficacy of therapeutic strategies, and long-term patient and renal outcomes including post-transplant disease recurrence.